2015
DOI: 10.1155/2015/742686
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Distribution of Vitreoretinal Interface Abnormalities among Urban Community Population in China

Abstract: The aim of this research was to identify the prevalence and distribution of vitreoretinal interface abnormalities (VIAs) among urban community population in Shenyang, China. According to the WHO criteria, a cross-sectional study was carried out among 304 Type 2 diabetes (T2D) patients and 304 people without diabetes as control over 45 years old. The presence of VIAs was determined by standardized grading of macular optical coherence tomography (Optovue OCT; Optovue, Inc., Fremont, CA) scans and two-field fundu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“… 14 19 China is one of the most rapidly aging societies in the world, and the prevalence rate of ERM is estimated to be 7.3%–11.43%. 18 , 19 Moreover, with the adoption of the 23G system (a more refined vitrectomy system), and more sophisticated OCT instruments and staining techniques, 4 the prognosis for macular diseases treated with PPV has improved in recent years. Therefore, more patients with ERM and MH prefer PPV than conservative treatment, which is another reason for the increase in the rate of macular diseases treated with PPV.…”
Section: Discussionmentioning
confidence: 99%
“… 14 19 China is one of the most rapidly aging societies in the world, and the prevalence rate of ERM is estimated to be 7.3%–11.43%. 18 , 19 Moreover, with the adoption of the 23G system (a more refined vitrectomy system), and more sophisticated OCT instruments and staining techniques, 4 the prognosis for macular diseases treated with PPV has improved in recent years. Therefore, more patients with ERM and MH prefer PPV than conservative treatment, which is another reason for the increase in the rate of macular diseases treated with PPV.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost 40% of the cases in that series had vitreomacular adhesion alone. In an urban Chinese population, Liu et al 11 reported a prevalence of 16.8% for any VRIA among adults without eye disease, excluding eyes with posterior vitreous detachment alone. Meuer et al 12 reported a prevalence of 39.7% for any VRIA, excluding macular and paravascular cysts, among the residents of Beaver Dam.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PVD is mainly affected by the age of the patients, but there are also other known risk factors including: greater eye length and myopia, aphakia, inflammatory diseases, eye traumas, and ocular surgery [11]. World literature provides data indicating a higher prevalence of PVD in patients with type 2 diabetes compared to non-diabetic patients [12,13]. The results of our study indicate that also prediabetes should be considered as a factor favouring the posterior vitreous detachment.…”
Section: Discussionmentioning
confidence: 99%